STYLISTIC DEVICES IN MODERN MUSIC: AN ANALYSIS OF FIGURATIVE LANGUAGE IN “BABY QUEEN” BY GORILLAZ - Muqtafin, Muhammad Zaki; Tergun, Prabu Barry Alamsyah; Rosalinah, Yanti (Elite : English and Literature Journal, 2025)
This study investigates the use of figurative language in the song “Baby Queen” by Gorillaz. The research aims to identify and analyze the types of figurative language used in the lyrics and to explore their contribution to the song’s emotional and interpretative depth. The analysis employs several methods from several theorists, including data reduction, data presentation, and verification. The findings reveal 19 instances of figurative language throughout the song, comprising four metaphors, two personifications, three symbols, two hyperboles, two synecdoche, two repetitions, one allusion, and one instance of irony. Among these, metaphor emerges as the most dominant type, suggesting that the songwriter employs comparison as a key expressive device to convey complex ideas and emotions. The use of various figurative forms enriches the song’s lyrical quality, enhancing its emotional appeal and allowing for multiple layers of interpretation. Through these stylistic choices, Gorillaz successfully evoke imagination and invite listeners to engage in deeper speculation about the meaning behind the lyrics. This research not only contributes to the understanding of how figurative language functions in song lyrics but also serves as a useful reference for students and readers interested in literary analysis. It is hoped that this study will foster a deeper appreciation of figurative expression in modern music.